REKONSTRUKSI FILSAFAT MATEMATIKA DALAM PEMBELAJARAN BERBASIS TEKNOLOGI UNTUK MATERI PENDIDIKAN KONTEMPORER - Anggi Anatasia Kinanti; Mislah Nasution; Sartika Manurung (MES: Journal of Mathematics Education and Science, 2026)
The development of digital technology and the demands of 21st-century competencies require mathematics learning to move beyond procedural approaches. This article aims to compile a conceptual and empirical synthesis of the integration of mathematical philosophy and information technology-based learning, as well as to test its influence through comparative simulation analysis. The study was conducted through a systematic literature review of research related to the philosophy of mathematics, humanistic and constructivist approaches, and IT-based learning models. To strengthen the empirical argument, a paired t-test simulation was conducted based on the average score increase reported in various experimental studies. The findings indicate that the integration of philosophical and technological approaches is not only statistically significant but also substantively pedagogical. Theoretically, these results confirm that an epistemological paradigm shift—from knowledge transmission to active construction—is a key factor in improving learning outcomes. Thus, the effectiveness of technology-based learning is highly dependent on its underlying philosophical foundation.